Pastoralist Voices on Climate Change - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
A Maasai woman talks about how she has learned how to shoot and produce videos, as a project to show Maasai people talking about how the climate has changed. The film "Pastoralist Voices on Climate Change," created by Joana Roque de Pinho, Lindsay Simpson and Nicolas Tapia, illustrates the challenges that pastoralists face in a changing climate. Read more on our blog: https://ccafs.cgiar.org/blog/pastoralist-voices-climate-change